Ex-post evaluation study of IFPRI’s research on high-value agriculture, 1994–2010 - Kydd, Jonathon (International Food Policy Research Institute, 2015)
This paper reports on an ex-post assessment of IFPRI’s research on High-Value Agriculture (HVA) over 1994–2010. HVA is defined to include perishable agricultural commodities produced for the market that yield high returns to land, labor, or both. IFPRI’s research on HVA has been housed mainly in GRP27 (Participation in high value agricultural markets). Questions for the study included whether IFPRI had the right research strategy for this topic; was focused on the right issues; was a leader in the field; used the most relevant approaches and methods; and was successful in sensitizing/influ-encing the policies of governments, agribusiness, academia, civil society, and the international donor community. Finally, what has been the impact of the HVA policies that IFPRI influenced?